Post-tooth extraction induction effect of Moringa oleifera leaf extract and demineralized freeze-dried bovine bone xenograft treatment on alveolar bone trabecula area - Utari Kresnoadi; Najla Salsabila; Primanda Nur Rahmania; Phara Aster Chandra Adventia; Bima Subiakto Rahmani; Nobuhiro Yoda (Dental Journal, 2023)
Background: After tooth extraction, alveolar bone resorption occurs naturally, followed by alveolar bone remodeling. Alveolar bone formation is characterized by an increase in density and expansion of the trabecular bone. Socket preservation using a combination of Moringa oleifera leaf extract and demineralized freeze-dried bovine bone xenograft (DFDBBX) is expected to increase the area of the alveolar bone trabeculae and thus accelerate the process of alveolar bone formation. Purpose: This study aimed to determine if a combination of Moringa oleifera leaf extract and DFDBBX could increase the area of the alveolar bone trabeculae in tooth extraction sockets. Methods: With their lower left incisors extracted, the 56 Cavia cobayas were divided into eight treatment groups according to the material given: polyethylene glycol (PEG), DFDBBX and PEG, Moringa oleifera leaf extract and PEG, and a combination of Moringa oleifera leaf extract, DFDBBX, and PEG. On the seventh and thirtieth days, the Cavia cobayas were sacrificed and examined. Histopathological samples were stained with Hematoxylin-Eosin (HE) to evaluate the trabecula area, and data were analyzed using one-way ANOVA and Tukey HSD. Results: On the thirtieth day, the group that received a combination of Moringa oleifera leaf extract and DFDBBX had the greatest area of alveolar bone trabeculae. Conclusion: A combination of Moringa oleifera leaf extract and DFDBBX induced in the tooth extraction socket can increase the area of the alveolar bone trabeculae.